Impact of aerobic exercise on sleep and motor skills in children with autism spectrum disorders – a pilot study - Br (Dove Medical Press, 2015)
Serge Brand,1,2,* Stefanie Jossen,2,* Edith Holsboer-Trachsler,1 Uwe Pühse,2 Markus Gerber21Psychiatric Clinics of the University of Basel, Center for Affective, Stress and Sleep Disorders (ZASS), 2Department of Sport, Exercise and Health, Sport Science Section, University of Basel, Basel, Switzerland*These authors contributed equally to this work and share the first authorshipBackground: Prevalence rates of autism spectrum disorder (ASD) have increased dramatically in the last two decades. In addition to the core symptoms such as impaired communication, difficulties in social interaction, and restricted and stereotypical patterns of behavior and interests, poor sleep and motor skill (MS) deficits have also been observed in children with ASD. On the other hand, there is evidence that aerobic exercise training (AET) has a positive impact on sleep, and that specific training improves MSs. Accordingly, the aim of the present pilot study was to investigate to what extent a combination of AET and MS training (MST) would improve sleep and physical performance in a small sample of children with ASD. Method: Ten children with ASD (mean age: 10 years) took part in the study. After a thorough medical examination and psychiatric assessment, children participated in thrice-weekly 60-minute sessions of AET and MST lasting for 3 consecutive weeks. Sleep was assessed both objectively (sleep-encephalography [sleep-EEG]) and subjectively (parents’ questionnaire). MSs were assessed via standardized test batteries. Parents completed sleep and mood logs, and ratings of mood. Results: Mild-to-moderate insomnia was reported in 70% of children. Compared to nights without previous AET and MS, on nights following AET and MS, sleep efficiency increased (d=1.07), sleep onset latency shortened (d=0.38), and wake time after sleep onset decreased for 63% of the sample (d=1.09), as assessed via sleep-EEG. Mood in the morning, as rated by parents, improved after three weeks (d=0.90), as did MSs (ball playing, balance exercise: ds>0.6).Conclusion: The pattern of results of this pilot study suggests that regular AET and MST impact positively on sleep, MSs, and mood among children with ASD.Keywords: physical activity, ball playing, balancing, insomnia, sleep efficiency, autism spectrum disorder, sleep-EEG